Role of perfusion index in pulse oximetry screening for critical congenital heart disease in neonates - Ramesh, S; Kumutha, J (Indian Journal of Child Health, 2018)
Introduction: Screening for critical congenital heart diseases (CCHD) with oxygen saturation (SpO2) by pulse oximeter often misses left-sided obstructive heart diseases. Objective: The role of perfusion index (PI) along with SpO2 in CCHD screening was studied. Methodology: The Masimo, RADICAL-7 pulse oximeter was used to record the SpO2 and PI in the right hand and left foot of asymptomatic babies at 24–72 h of life. Babies with SpO2 <95% or PI <0.7 were rechecked at an hourly interval for three recordings. SpO2 90–94% or PI <0.7 in all three recordings or SpO2 <90% at any one recording were considered as screen positive. An echocardiogram was done for screen-positive cases. Screen negative cases were clinically followed for 6 weeks. Result: Of 1011 screened babies, four were screen positive. One baby had PI <0.7 and SpO2 <90%. This baby had single ventricle, transposed great vessels, and interrupted aortic arch. Other three cases had SpO2 between 90% and 94% in all three recordings. Echocardiogram showed severe right ventricle outflow obstruction in 2 cases and normal heart in one baby. At follow-up, no baby had CCHD. Conclusion: In this study with small sample size, only one baby had left-sided obstructive lesion but also had single ventricle physiology. Hence, there was no difference in the diagnostic accuracy between SpO2 alone and SpO2 with PI in screening for CCHD. Thus, combining PI with SpO2 may improve CCHD screening using pulse oximeter, but large-scale study is needed.